(untitled) (Historia, 2021)
This article examines the activities of the non-governmental sector of the South African environmental movement between the United Nations Conference on the Human Environment (Stockholm) in 1972 and the Earth Summit (Rio de Janeiro) in 1992. During this period non-governmental environmental organisations in South Africa gradually moved away from its predominantly conservation-based environmental agenda that was apolitical and important mostly to white people, to an environmental agenda that, by the late 1980s, was highly emotive, politically charged and racially inclusive. The twenty years under discussion is divided into three periods: 1972-1982 during which time the white conservation agenda dominated; 1982-1988 in which the non-governmental sector gradually started to move towards an environmental justice agenda, and 1988-1992 which was dominated by highly political and emotive environmental struggles against various environmental problems in South Africa.